Understanding and nurturing the missionary family - Echerd, Pam; Arathoon, Alice (Pasadena, CA William Carey Library, 1989)
Includes index.
Compendium of the International Conference on Missionary Kids, Quito, Ecuador, January 4-8, 1987
Keywords: Missionary kids -- nurture of; Missionaries -- families -- counselling